The purpose of this rese8fCh were to know about fisheries commen;e condition at Batang Regency, especially at the target area of this program. And also analyze about income differences between fish sellers and fish processors who receives and unreceives funds donations from PEMP programs. This research was held at Kelurahan Proyonanggan Utara, Desa Klidang Lor, Batang District and Desa Ujung Negoro, Tulis District from December 2002 - February 2003. The method of this research was descriptive - Dian Ayunita N N D; Abdul Kohar Mudzakir (Buletin Ekonomi Perikanan, 2006)
The purpose of this rese8fCh were to know about fisheries commen;e condition at Batang Regency, especially at the target area of this program. And also analyze about income differences between fish sellers and fish processors who receives and unreceives funds donations from PEMP programs. This research was held at Kelurahan Proyonanggan Utara, Desa Klidang Lor, Batang District and Desa Ujung Negoro, Tulis District from December 2002 - February 2003.   The method of this research was descriptive method which concern on a case study. The samples were obtained by proportional stratified random sampling. The stratification classified based on their commen;e scale were small, medium, and big scale. To analize data used Wilcoxon Sum Quadrate test with quare" test 0,05.'   The result showed that the condition of fisheries commen;e at the target area of this programs have potency to enlarge. This based on fisheries total production data that increase from 2000- 2001 and much people in the target area who still depend their live from fisheries sector. Income of fish sellerslfish piocessors who receives and unreceives funds donations from PEMP programs at small scale showed that was totally different. At medium scale both of groups income's were not different. And also at the big scale gaven the same Iftsult with medium scale, it were not different.